English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I'm prepping for a midterm; I'll apreciate your help to help me get this concept which escapes me at the moment.

2007-01-30 12:52:03 · 8 answers · asked by RogerDodger 1 in Science & Mathematics Mathematics

8 answers

because 27^(1/3) =3
[the 1/3 power is the cube root]

in general log(base b) A = X when b^X = A

2007-01-30 12:58:56 · answer #1 · answered by davidosterberg1 6 · 0 0

When you rewrite log(base 27) 3 = (1/3) as an exponential equation it becomes

27 ^ (1/3) = 3

Since 1/3 as an exponent means the cube root, the cube root of 27 is 3.

2007-01-30 13:02:19 · answer #2 · answered by hayharbr 7 · 0 0

hope u remember this rule

log(base a) a = 1

so log(base 27)3 = log(base 27) 27^(1/3)

i just substituted 3 = 27^(1/3)

so now i have the base number and the log number the same so i move 1/3 before log to get

(1/3)log(base 27) 27 = (1/3) * 1 by the rule i stated

= 1/3

2007-01-30 13:01:28 · answer #3 · answered by wendywei85 3 · 0 0

(a million/3)^2 - x = 27 -x = 27 - (a million/3)^2 x = (a million/3)^2 - 27 possibly you meant (a million/3)^(2 - x) = 27. for that reason, (a million/3)^(2 - x) = 27 (a million/3)^(2 - x) = (a million/3)^(-3) 2 - x = -3 -x = -5 x = 5

2016-12-13 04:55:37 · answer #4 · answered by killeen 4 · 0 0

Logarithms are the inverses of exponents. So every logarithm is equal to an exponent.

log(base 27) 3 = (1/3)

Above the log is equal to (1/3), when we rewrite it in exponential form the (1/3) will be the exponent to which the base is raised.

3^(1/3) = 27.

It's not the easiest concept in the world to fully understand, but as long as you always come back to the fact that logarithms are exponents, it will help with logarithmic computations and rewriting them.

2007-01-30 13:03:20 · answer #5 · answered by mirramai 3 · 0 1

log(base27) 3 = 1/3


Log definition :

log(base b) x = y <=> b ^ y = x





log(base 27) 3 = 1/3

27 ^ 1/3 = 3 (by log definition)

(3^3 )^1/3 = 3

3 ^3/3 = 3

3^1 = 3

3 = 3 (equality is true)

2007-01-30 13:10:02 · answer #6 · answered by frank 7 · 0 0

Let's rewrite this as exponential form. This mean that
27^(1/3)=3
This is right beacause raise a number to one-third is like taking the cube root.
So what is the cube root of 27. The answer is three.

2007-01-30 13:00:47 · answer #7 · answered by Jose G D 2 · 0 0

log(base b)(a) = c and a = b^c
so...
3 = 27^1/3 or the cubed root of 27 = 3.

2007-01-30 13:02:56 · answer #8 · answered by Anton 3 · 0 0

fedest.com, questions and answers